201 Interagency collaboration for the identification of road safety research priorities in Nepal. (20th November 2022) - Mytton, Julie; Pant, Puspa; Rana, Pranita; Pradhan, Kriti; Joshi, Sunil Kumar
Abstract : Background/Aims: Road traffic injuries are increasing in Nepal with the rapid expansion of roads and traffic and despite current road safety legislation. The aim of this study was to identify and prioritise the research needed to help Nepali agencies develop an improved road safety system. Methods: Using Delphi methodology, stakeholders from government institutions, academia, engineering, healthcare and civil society were interviewed to identify knowledge gaps and areas for potential research. Participants completed two rounds of ranking of identified research questions. Results: 93 participants took part, grouped according to their expertise and the five World Health Organisation's 'pillars' of road safety: 1) Road Safety Management; 2) Safer Roads; 3) Safer Vehicles; 4) Safer Road Users and 5) effective post-crash response. Interviews yielded 1019 research suggestions. Ranking within expert groups yielded consensus on the important questions for each pillar. A workshop involving all participants identified 6 questions considered the most urgent: (1) How can implementing agencies be made more accountable? (2) How should different types of roads be designed to make them safer for all road users? (3) What vehicle fitness factors lead to traffic crashes? (4) How can the driver licensing system be improved to ensure safer drivers? (5) What factors lead to public vehicle crashes and how can they be addressed? (6) What factors affect emergency response services getting to the patient and getting them to the right hospital in the best time? Conclusions: Working across sectors yielded a breadth of perspectives to identify priorities for future road safety research.